Impact of drug transporters on cellular resistance towards saquinavir and darunavir - König, Sonja Katharina; Herzog, Melanie; Theile, Dirk; Zembruski, Nadine Cécile Luise; Haefeli, Walter E.; Weiß, Johanna (The journal of antimicrobial chemotherapy, 2010)
Highly active antiretroviral therapy is complicated by drug-drug interactions and the development of viral resistance. Drug interactions involve transporters that may critically affect the pharmacokinetics of many antiretroviral drugs and contribute to the formation of functional sanctuary sites. We therefore investigated the effect of saquinavir and darunavir on drug transporter expression and functional consequences for cellular resistance towards these compounds.